A Method to Discriminate Between the Candida stellata and Saccharomyces cerevisiae in Mixed Fermentation on WLD and Lysine Agar Media - Di Maio, S.; Polizzotto, G.; Planeta, D.; Oliva, D. (South African Journal of Enology and Viticulture, 2016)
This paper presents a simple method to distinguish between Candida stellata and Saccharomyces cerevisiae yeasts during microbiological analyses. The method is based on differential yeast growth on a medium containing cycloheximide and a medium containing lysine as only nitrogen source (lysine agar). The cycloheximide resistance of 45 yeast strains belonging to Candida stellata, Hanseniaspora uvarum, Hanseniaspora guilliermondii, Metschnikowia pulcherrima, Torulaspora delbrueckii, Zygosaccharomyces bailii, Kluyveromyces thermotolerans and Zygoascus hellenicus, and 14 strains of Saccharomyces cerevisiae and Saccharomyces bayanus on WL nutrient agar, was assayed. Cycloheximide resistance is characteristic of the species H. uvarum, H. guilliermondii and Z. hellenicus, while for the other yeasts it depends on the strain and the concentration of cycloheximide used. Two mg/L of cycloheximide allows selective counting of a strain of C. stellata (Cs3) compared to one of the sensitive S. cerevisiae strain (NDA21). Similar results can be obtained on lysine agar, but counts are reliable only with the additional spreading of a monolayer of Saccharomyces cells. The different cycloheximide resistance of C. stellata and S. cerevisiae can be used in the microbiological analysis of mixed cultures to monitor the individual growth of the two yeast species. This method can be applied to the study of mixed fermentations with other non-Saccharomyces species. The modified use of lysine agar is useful to a certain extent in the distinction of multistarter yeasts from the indigenous yeasts.